Management of glioblastoma: comparison of clinical practices and cost‐effectiveness in two cohorts of patients (2008 versus 2004) diagnosed in a French university hospital. (28th August 2014) - Diebold, G.; Ducray, F.; Henaine, A.‐M.; Frappaz, D.; Guyotat, J.; Cartalat‐Carel, S.; Breant, V.; Fouquet, A.; Aulagner, G.; Honnorat, J.; Armoiry, X.
Summary What is known and objective Therapeutic options for the management of glioblastoma (GBM) have greatly evolved over the last decade with the emergence of new regimens combining radiotherapy plus temozolomide and the use of bevacizumab at recurrence. Our aim was to assess the clinical and economic impacts of those novel strategies in our center. Methods A single‐center retrospective chart review was conducted on patients newly diagnosed with a GBM over two periods (year 2004, group 1 or year 2008, group 2) with limitations to those eligible to radiotherapy after initial diagnosis. The type of medical management was described and compared, as well as overall survival and total costs from diagnosis to death or the last follow‐up date. Cost analysis was performed under the French Sickness Fund perspective using tariffs from 2012. Results One hundred twenty‐two patients were selected (49 in group 1 and 73 in group 2) with similar baseline characteristics within the two groups. Patients from group 2 received more frequently temozolomide radiochemotherapy (71% vs. 39%, P < 0·05) as first‐line treatment as well as bevacizumab regimen at recurrence (48% vs. 6%, P < 0·05); the median overall survival was increased between the two periods (respectively 17 vs. 10 months, P < 0·05). The mean total cost per patient was 54 388 € in group 1 and 71 148 € in group 2 (P < 0·05). Hospital care represented the largest expenditure (76% and 58% in groups 1 and 2 respectively) followed by chemotherapy drugs costs (11% and 30% respectively). The total cost difference between the two groups was explained by the increasing use of temozolomide and bevacizumab. The incremental cost‐effectiveness ratio was estimated at 54 355 € per life‐year gained. What is new and conclusion As far as we know, this is the first study reporting the total cost of GBM management based on the French perspective, as well as the cost‐effectiveness of clinical practices in term of cost per life‐year gained. Those novel strategies have contributed to improve overall survival while inducing a substantial, but acceptable, increase of total costs.